A pressure-production integrated emulsion fracturing fluid
By modifying thickeners composed of polyacrylamide and casein, combining crosslinking agents and surfactants to form a colloidal network, the problems of poor shear resistance and poor sand carrying properties at high temperatures are solved. It realizes efficient oil and gas mining and environmentally friendly fracturing fluid.
Patent Information
- Application Number
- CN202411245285.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The existing fracturing fluid has poor shear resistance, large friction resistance and poor sand carrying performance at high temperatures, which has a great pollution to the formation and is difficult to meet the needs of efficient transformation of oil extraction.
Use thickeners composed of modified polyacrylamide, casein, xanthan gum, konjac gum, etc., combined with crosslinking agents such as dithiobismaleimideethane and 2,5-furandimethanol and surfactant The agent is formed by plasma treatment and colloidal network to improve viscosity and stability and reduce friction.
It significantly improves the shear resistance, high temperature resistance and sand carrying properties of the fracturing fluid, reduces pollution to the formation, improves oil and gas production and fluidity, and is in line with the trend of environmental protection and sustainable development.
Smart Images

Figure CN118755466B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fracturing fluid, and in particular to a pressure-production integrated emulsion fracturing fluid. Background Art
[0002] Fracturing is a process technology for transforming the seepage characteristics of oil layers. It is an important measure for increasing the production of oil and gas wells and increasing the injection of solvent wells. Fracturing fluid is an indispensable working fluid in the fracturing process. It is the working fluid used in the fracturing transformation of oil and gas layers in order to increase the crack area of the well wall and improve the extraction efficiency of crude oil and natural gas during the petroleum and gas production process. It is a heterogeneous and unstable chemical system made of a variety of additives in proportion. It is transmitted to the formation through the high pressure formed by ground equipment, causing the formation to break and form cracks, and transporting proppants along the cracks. Fracturing fluid, as a key fluid in fracturing and transforming reservoirs, needs to have excellent viscoelasticity and temperature resistance. Fracturing fluid The performance directly affects the fracturing effect and the injection and production capacity of the well. At present, there are mainly water-based fracturing fluids, oil-based fracturing fluids, emulsified fracturing fluids, viscoelastic surfactant fracturing fluids, etc. on the market. Water-based fracturing fluids need to add a variety of additives during construction, which increases operating errors and work costs, makes the process more complicated, and increases instability. At the same time, water-based fracturing fluids have poor temperature resistance and shear resistance. Oil-based fracturing fluids are flammable because their main components are oils, and have poor temperature resistance, large filtration loss, and poor construction safety. Emulsified fracturing fluids have large friction and poor thermal stability. Viscoelastic surfactant fracturing fluids have poor sand carrying performance and insufficient temperature resistance.
[0003] Publication No. CN 111253927 A discloses an emulsion-type fracturing fluid and a preparation method thereof. The raw materials of the emulsion-type fracturing fluid include a thickener, a breaker and water. The emulsion-type fracturing fluid includes the following components: by mass percentage, 1.1-1.2% thickener, 0.02-0.04% breaker, and the balance is water. The present invention also relates to a preparation method of the emulsion-type fracturing fluid, which includes: step 1: adding a thickener to water under stirring, stirring evenly to obtain a raw gel solution, and then standing for 10 minutes; step 2: adding a breaker according to the concentration of the thickener and the temperature of the water bath to obtain a fracturing fluid. The emulsion-type fracturing fluid has fewer components, dissolves quickly, is easy to prepare, and improves the preparation efficiency of traditional fracturing fluids. A breaker is added during the preparation of the fracturing fluid. The breaker destroys the fracturing fluid during the sand-carrying process of the fracturing fluid, causing its viscoelasticity to decrease, thereby causing the shear performance of the fracturing fluid to decrease, affecting the fracturing mining effect.
[0004] Therefore, solving the technical problems that the oil extraction fracturing fluid industry urgently needs to solve include high temperature resistance, poor shear resistance, high friction, poor sand carrying performance, and high formation pollution. Summary of the invention
[0005] The purpose of the present invention is to provide an integrated pressure-production emulsion fracturing fluid to solve the problems of poor shear resistance, poor high temperature resistance, high friction, poor sand carrying performance, and high formation pollution proposed in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solution: a pressure-production integrated emulsion fracturing fluid, comprising the following components: a thickener, a cross-linking agent, and a surfactant;
[0007] Furthermore, the thickener is prepared by mixing modified polyacrylamide, casein, xanthan gum, konjac gum and water in proportion;
[0008] Furthermore, the modified polyacrylamide is modified by the following method: placing the polyacrylamide in a plasma equipment treatment chamber, subjecting the polyacrylamide to plasma treatment, wherein the plasma equipment power is 930-950W and the charge density is 950-970 / cm 3 , gas flow rate is 1.2-1.4L / min, processing chamber pressure is 85-90kPa, processing chamber temperature is 58-62℃, and processing time is 160-190s;
[0009] Furthermore, the casein is prepared by the following method: adding 6.5-6.8% organic acid (lactic acid: acetic acid mass ratio 1:1.2) to skimmed pure milk, stirring and adjusting the pH value to 4.7-4.8, causing the casein to coagulate and precipitate, filtering and centrifuging to obtain the casein;
[0010] Furthermore, the cross-linking agent is prepared by mixing disulfide bismaleimide ethane, nano-organic zirconium, nano-organic boron, sodium phosphate and water in proportion;
[0011] Furthermore, the surfactant is prepared by mixing 2,5-furan dimethanol, alkyl glycoside, alkyl dimethyl betaine, polyethylene glycol and sodium dodecyl sulfate in proportion.
[0012] Furthermore, the pressure-production integrated emulsion fracturing fluid is prepared by the following method:
[0013] S1, thickener preparation: Weigh 30-34 parts by weight of modified polyacrylamide, 28-30 parts by weight of casein, 20-22 parts by weight of xanthan gum, 16-18 parts by weight of konjac gum, and 92-95 parts by weight of water, place in a reactor and mix and stir, the reactor temperature is 50-55° C., the stirring speed is 720-750 rpm, and the stirring time is 18-22 minutes to obtain a thickener;
[0014] S2. Preparation of crosslinking agent: 20-23 parts by weight of disulfide bismaleimide ethane, 13-16 parts by weight of nano-organic zirconium (composed of tetra-n-propyl zirconate and zirconium acetylacetonate in a mass ratio of 1:1), 9-10 parts by weight of nano-organic boron (composed of organic boric acid and organic boron ester in a mass ratio of 1:1.5), 3-5 parts by weight of sodium phosphate, and 55-60 parts by weight of water were weighed and mixed in a homogenizer to obtain a crosslinking agent solution at a speed of 500-550 rpm;
[0015] S3, surfactant preparation: weigh 18-25 parts by weight of 2,5-furan dimethanol, 12-16 parts by weight of alkyl glycoside, 10-15 parts by weight of alkyl dimethyl betaine, 8-12 parts by weight of polyethylene glycol, and 7-10 parts by weight of sodium lauryl sulfate, and mix them evenly in a blender to obtain a surfactant;
[0016] S4. Place the thickener prepared by S1 in a reactor, slowly add 45-50 parts of the cross-linker solution prepared by S2 into the reactor, mix and stir for 48-55 minutes at a stirring speed of 1200-1230 rpm, let stand for 30-35 minutes, then add 15-20 parts of the surfactant prepared by S3, mix and stir for 20-25 minutes at a stirring speed of 950-980 rpm, and keep the reactor temperature at 50-55°C to obtain an emulsion fracturing fluid.
[0017] As a preferred technical solution of the present invention, the particle size of the nano-organic zirconium and nano-organic boron is 550-600 nm.
[0018] As a preferred technical solution of the present invention, the moisture content of casein is 6.5-7.5%.
[0019] As a preferred technical solution of the present invention, the particle size of the 2,5-furan dimethanol is 500 mesh.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention treats polyacrylamide with plasma, and high-energy particles in the plasma, such as electrons, ions, and free radicals, collide and react with the surface of polyacrylamide to form a uniform chemical structure layer on the surface of polyacrylamide, thereby improving the hydrophilicity and activity of the surface of polyacrylamide, thereby enhancing its interaction with other components in the fracturing fluid, improving its chemical stability, thermal stability, and shear resistance, and reducing the degradation and failure of the fracturing fluid during the fracturing process.
[0022] 2. The present invention extracts casein from skim milk as a raw material for producing fracturing fluid. The casein substructure contains hydrophilic groups and hydrophobic groups. This structure enables casein to form hydrogen bonds or other interactions with water molecules, enhances the binding force between casein and water molecules, and forms a stable colloidal network. In a high temperature and high salt environment, this colloidal network can remain relatively stable, prevent the effective ingredients in the fracturing fluid from precipitating or separating out, and improve the temperature resistance and salt resistance of the fracturing fluid. At the same time, casein has an emulsifying effect, which can improve the compatibility of the fracturing fluid with other additives or formation fluids and improve the overall performance of the fracturing fluid. Casein can synergize with other chemical substances (such as polymers, cross-linking agents, etc.) to improve the performance of the fracturing fluid, so that it can still maintain good fluidity and suspension in a high temperature and high salt environment, and improve the sand carrying capacity and shear resistance of the fracturing fluid. At the same time, casein is a natural protein with good biodegradability, which helps to reduce the pollution of the fracturing fluid to the environment.
[0023] 3. The present invention adds disulfide bismaleimide ethane and 2,5-furan dimethanol to the fracturing fluid. The maleimide cross-linking agent is a compound with a maleimide group, which can react with sulfhydryl groups such as cysteine residues in casein to form a stable covalent bond, realize intermolecular cross-linking, and react with high molecular compounds (such as polymers, natural rubber, etc.) to form a three-dimensional network structure, increase the viscosity and strength of the fracturing fluid, better resist fluid flow, and more effectively carry and transport proppants to ensure that the proppants are evenly distributed in the cracks. Improve the conductivity and oil and gas production of fractures; 2,5-furan dimethanol can reduce the surface and interfacial tension of liquids, help improve the fluidity of fracturing fluids, reduce frictional resistance, and improve fracturing efficiency. At the same time, 2,5-furan dimethanol is a biomass-based furan derivative compound, which is renewable and biodegradable, has little impact on the environment, and is in line with the current trend of environmental protection and sustainable development. The present invention uses a variety of thickeners, cross-linking agents, and surfactants in combination to improve the sand carrying capacity, shear resistance, and high temperature resistance of the fracturing fluid, reduce frictional resistance, and have little pollution to the surface and the environment.
[0024] 4. The present invention is to mix the thickener, the crosslinker and the surfactant in proportion and evenly, first mix the thickener in the reactor, then add the crosslinker to react with the thickener, let it stand and then add the surfactant to prepare the fracturing fluid in this order. Adding the thickener first can ensure that it is fully dissolved and swollen in water, so that the subsequent addition of the crosslinker can react more evenly and avoid excessive or insufficient local crosslinking. Letting it stand for a period of time after the crosslinking reaction is conducive to the further progress of the crosslinking reaction and forming a more stable polymer grid structure. The surfactant plays the role of reducing surface tension and improving stability in the fracturing fluid. Adding the surfactant after the crosslinking reaction is completed can further optimize the performance of the fracturing fluid. If the surfactant is added at the same time as the thickener or the crosslinker, it may react in advance and affect the performance of the fracturing fluid. Adding the surfactant later can ensure that it will play a role after the crosslinking reaction is completed to avoid unnecessary interference. At the same time, the present invention strictly controls the reaction temperature, rotation speed and time in each reaction to improve the mixed reaction effect of the fracturing fluid. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a flow chart for preparing the emulsion fracturing fluid of the present invention;
[0026] Figure 2 It is a bar graph of the drag reduction rate of the emulsion fracturing fluid of the present invention;
[0027] Figure 3 It is a bar graph of the sedimentation rate of the ceramsite proppant of the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The present invention subjects polyacrylamide to plasma treatment, and high-energy particles in the plasma, such as electrons, ions, free radicals, etc., collide and react with the surface of the polyacrylamide to form a uniform chemical structure layer on the surface of the polyacrylamide, thereby improving the hydrophilicity and activity of the surface of the polyacrylamide, thereby enhancing its interaction with other components in the fracturing fluid, improving its chemical stability, thermal stability and shear resistance, and reducing the degradation and failure of the fracturing fluid during the fracturing process.
[0030] The present invention extracts casein from skimmed milk as a raw material for producing fracturing fluid. The casein substructure contains hydrophilic groups and hydrophobic groups. This structure can enable casein to form hydrogen bonds or other interactions with water molecules, enhance the binding force between casein and water molecules, and form a stable colloidal network. In a high temperature and high salt environment, this colloidal network can remain relatively stable, prevent effective components in the fracturing fluid from precipitating or separating out, and improve the temperature resistance and salt resistance of the fracturing fluid. At the same time, casein has an emulsifying effect, can improve the compatibility of the fracturing fluid with other additives or formation fluids, and improve the overall performance of the fracturing fluid. Casein can synergize with other chemical substances (such as polymers, cross-linking agents, etc.) to improve the performance of the fracturing fluid, so that the fracturing fluid can still maintain good fluidity and suspension in a high temperature and high salt environment, and improve the sand carrying capacity and shear resistance of the fracturing fluid. At the same time, casein is extracted from milk, is a natural protein, has good biodegradability, and is helpful to reduce the pollution of the fracturing fluid to the environment.
[0031] The present invention adds disulfide bismaleimide ethane and 2,5-furan dimethanol to the fracturing fluid. The maleimide cross-linking agent is a compound with a maleimide group, which can react with a thiol group such as a cysteine residue in casein to form a stable covalent bond, realize cross-linking between molecules, and react with a high molecular compound (such as a polymer, natural rubber, etc.) to form a three-dimensional network structure, significantly increase the viscosity and strength of the fracturing fluid, better resist fluid flow, and more effectively carry and transport proppants, ensure that the proppants are evenly distributed in the cracks, and improve The conductivity of the fracture and the oil and gas production; 2,5-furan dimethanol can reduce the surface and interfacial tension of the liquid, which is helpful to improve the fluidity of the fracturing fluid, reduce friction and improve the fracturing efficiency. At the same time, 2,5-furan dimethanol is a biomass-based furan derivative compound, which is renewable and biodegradable, reduces the impact on the environment, and conforms to the current trend of environmental protection and sustainable development. The present invention uses a variety of thickeners, cross-linking agents, and surfactants in combination, which can improve the sand carrying capacity, shear resistance, and high temperature resistance of the fracturing fluid, reduce friction, and has little pollution to the surface and the environment.
[0032] The present invention is to mix the thickener, the cross-linking agent and the surfactant respectively in proportion and uniformly, first mix the thickener in a reactor, then add the cross-linking agent to react with the thickener, and then add the surfactant after standing to prepare the fracturing fluid. The thickener is added first to ensure that it is fully dissolved and swollen in water, so that the subsequent addition of the cross-linking agent can react more uniformly, avoiding excessive or insufficient local cross-linking. The cross-linking agent increases the viscosity of the fracturing fluid by cross-linking reaction with the thickener, and plays a role in carrying the proppant. The cross-linking reaction can form a network structure, reduce the amount of thickener used, and reduce the pollution to the formation. After the cross-linking reaction, it is left to stand for a period of time, which is conducive to the further progress and stability of the cross-linking reaction, forming a more stable polymer grid structure with surface active The surfactant plays the role of reducing surface tension and improving stability in the fracturing fluid, thereby improving the fracturing effect. Adding the surfactant after the cross-linking reaction is completed can further optimize the performance of the fracturing fluid, such as improving stability and reducing filtration loss. If the surfactant is added at the same time as the thickener or cross-linking agent, it may react in advance and affect the performance of the fracturing fluid. Adding it later can ensure that it will play a role after the cross-linking reaction is completed to avoid unnecessary interference. At the same time, the present invention strictly controls the reaction temperature, rotation speed and time in each reaction to improve the mixed reaction effect of the fracturing fluid. The thickener is first added to the fracturing fluid in the reactor, and then the cross-linking agent is added. The surfactant is added after standing, which can ensure that each component fully reacts and plays a role, thereby improving the performance and fracturing effect of the fracturing fluid.
[0033] The raw materials used in the present invention are all commercially available raw materials.
[0034] Embodiment 1
[0035] A pressure-production integrated emulsion fracturing fluid comprises the following components: a thickener, a cross-linking agent, and a surfactant, and is prepared by the following method:
[0036] Step 1: Modification of polyacrylamide: Place polyacrylamide in a plasma treatment chamber and perform plasma treatment on the polyacrylamide. The plasma power is 930W and the charge density is 950-970 / cm 3 , gas flow rate is 1.2-1.4 L / min, processing chamber pressure is 85 kPa, processing chamber temperature is 58 °C, and processing time is 190 s;
[0037] Step 2, casein preparation: add 6.5% organic acid (lactic acid: acetic acid mass ratio 1:1.2) to skim pure milk, stir and adjust the pH value to 4.7, so that the casein coagulates and precipitates, filter and centrifuge to obtain casein;
[0038] Step 3, preparation of thickener: 30 parts by weight of modified polyacrylamide, 28 parts by weight of casein, 20 parts by weight of xanthan gum, 16 parts by weight of konjac gum, and 92 parts by weight of water were weighed and placed in a reactor and mixed and stirred at a temperature of 50° C., a stirring speed of 720 rpm, and a stirring time of 18 minutes to obtain a thickener;
[0039] Step 4, preparation of cross-linking agent: 20 parts by weight of disulfide bismaleimide ethane, 13 parts by weight of nano-organic zirconium (composed of tetra-n-propyl zirconate and zirconium acetylacetonate in a mass ratio of 1:1), 9 parts by weight of nano-organic boron (composed of organic boric acid and organic boron ester in a mass ratio of 1:1.5), 3 parts by weight of sodium phosphate, and 55 parts by weight of water were weighed and placed in a homogenizer and mixed and homogenized to obtain a cross-linking agent solution, and the speed of the homogenizer was 500 rpm;
[0040] Step 5, preparation of surfactant: weigh 18 parts by weight of 2,5-furan dimethanol, 12 parts by weight of alkyl glycoside, 10 parts by weight of alkyl dimethyl betaine, 8 parts by weight of polyethylene glycol, and 7 parts by weight of sodium lauryl sulfate, and mix them in a blender to obtain a surfactant;
[0041] Step 6: Place the thickener prepared in step 3 in a reactor, slowly add 45 parts of the cross-linker solution prepared in step 4 into the reactor, mix and stir for 48 minutes at a stirring speed of 1230 rpm, let stand for 30 minutes, then add 15 parts by weight of the surfactant prepared in step 5, mix and stir for 20 minutes at a stirring speed of 980 rpm, and the reactor temperature is 50°C to obtain an emulsion fracturing fluid.
[0042] Embodiment 2
[0043] A pressure-production integrated emulsion fracturing fluid comprises the following components: a thickener, a cross-linking agent, and a surfactant, and is prepared by the following method:
[0044] Step 1: Modification of polyacrylamide: Place polyacrylamide in a plasma treatment chamber and perform plasma treatment on the polyacrylamide. The plasma power is 950W and the charge density is 950-970 / cm 3 , gas flow rate is 1.2-1.4 L / min, processing chamber pressure is 90 kPa, processing chamber temperature is 62 °C, and processing time is 160 s;
[0045] Step 2, casein preparation: add 6.8% organic acid (lactic acid: acetic acid mass ratio 1:1.2) to skim pure milk, stir and adjust the pH value to 4.8, so that casein coagulates and precipitates, filter and centrifuge to obtain casein;
[0046] Step 3, preparation of thickener: 34 parts by weight of modified polyacrylamide, 30 parts by weight of casein, 22 parts by weight of xanthan gum, 18 parts by weight of konjac gum, and 95 parts by weight of water were weighed and placed in a reactor, mixed and stirred at a temperature of 55° C., a stirring speed of 750 rpm, and a stirring time of 22 minutes to obtain a thickener;
[0047] Step 4, preparation of cross-linking agent: 23 parts by weight of disulfide bismaleimide ethane, 16 parts by weight of nano-organic zirconium (composed of tetra-n-propyl zirconate and zirconium acetylacetonate in a mass ratio of 1:1), 10 parts by weight of nano-organic boron (composed of organic boric acid and organic boron ester in a mass ratio of 1:1.5), 5 parts by weight of sodium phosphate, and 60 parts by weight of water were weighed and placed in a homogenizer and mixed to obtain a cross-linking agent solution. The speed of the homogenizer was 550 rpm.
[0048] Step 5, preparation of surfactant: weigh 25 parts by weight of 2,5-furan dimethanol, 16 parts by weight of alkyl glycoside, 15 parts by weight of alkyl dimethyl betaine, 12 parts by weight of polyethylene glycol, and 10 parts by weight of sodium lauryl sulfate, and mix them in a blender to obtain a surfactant;
[0049] Step 6: Place the thickener prepared in step 3 in a reactor, slowly add 50 parts by weight of the cross-linker solution prepared in step 4 into the reactor, mix and stir for 55 minutes at a stirring speed of 1200 rpm, let stand for 35 minutes, then add 20 parts by weight of the surfactant prepared in step 5, mix and stir for 25 minutes at a stirring speed of 950 rpm, and the reactor temperature is 55°C to obtain an emulsion fracturing fluid.
[0050] Embodiment 3
[0051] A pressure-production integrated emulsion fracturing fluid comprises the following components: a thickener, a cross-linking agent, and a surfactant, and is prepared by the following method:
[0052] Step 1: Modification of polyacrylamide: Place polyacrylamide in a plasma treatment chamber and perform plasma treatment on the polyacrylamide. The plasma power is 940W and the charge density is 950-970 / cm 3 , gas flow rate is 1.2-1.4 L / min, processing chamber pressure is 88 kPa, processing chamber temperature is 60 °C, and processing time is 180 s;
[0053] Step 2, casein preparation: add 6.6% organic acid (lactic acid: acetic acid mass ratio 1:1.2) to skim pure milk, stir and adjust the pH value to 4.7, so that casein coagulates and precipitates, filter and centrifuge to obtain casein;
[0054] Step 3, preparation of thickener: 32 parts by weight of modified polyacrylamide, 29 parts by weight of casein, 21 parts by weight of xanthan gum, 17 parts by weight of konjac gum, and 93 parts by weight of water were weighed and placed in a reactor and mixed and stirred at a temperature of 52° C., a stirring speed of 730 rpm, and a stirring time of 20 minutes to obtain a thickener;
[0055] Step 4, preparation of cross-linking agent: 22 parts by weight of disulfide bismaleimide ethane, 15 parts by weight of nano-organic zirconium (composed of tetra-n-propyl zirconate and zirconium acetylacetonate in a mass ratio of 1:1), 9.5 parts by weight of nano-organic boron (composed of organic boric acid and organic boron ester in a mass ratio of 1:1.5), 4 parts by weight of sodium phosphate, and 58 parts by weight of water were weighed and placed in a homogenizer for mixing and homogenization to obtain a cross-linking agent solution, and the speed of the homogenizer was 520 rpm;
[0056] Step 5, preparation of surfactant: weigh 20 parts by weight of 2,5-furan dimethanol, 15 parts by weight of alkyl glycoside, 12 parts by weight of alkyl dimethyl betaine, 10 parts by weight of polyethylene glycol, and 8 parts by weight of sodium lauryl sulfate, and mix them in a blender to obtain a surfactant;
[0057] Step 6: Place the thickener prepared in step 3 in a reactor, slowly add 46 parts by weight of the cross-linker solution prepared in step 4 into the reactor, mix and stir for 50 minutes at a stirring speed of 1220 rpm, let stand for 32 minutes, then add 18 parts by weight of the surfactant prepared in step 5, mix and stir for 23 minutes at a stirring speed of 960 rpm, and set the reactor temperature at 52°C to obtain an emulsion fracturing fluid.
[0058] Comparative Example 1:
[0059] The polyacrylamide of Example 2 is not modified by plasma treatment, and other method steps are the same as those of Example 2.
[0060] Comparative Example 2:
[0061] In Example 2, casein is not added, and other method steps are the same as in Example 2.
[0062] Comparative Example 3:
[0063] In Example 2, 2,5-furan dimethanol is not added, and other method steps are the same as in Example 2.
[0064] Comparative Example 4:
[0065] In Example 2, no disulfide bismaleimide ethane is added, and other method steps are the same as in Example 2.
[0066] The fracturing fluids prepared in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 and 4 were tested for their temperature and shear resistance using a rotational rheometer at a shear rate of 170 s -1As shown in Table 1, under the condition of shear temperature of 120°C, the fracturing fluids prepared in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 and 4 were sheared for 60 min, 90 min, 120 min, 150 min, 180 min, 210 min and 240 min, respectively. As the shear time increases, the apparent viscosity of the fracturing fluid decreases. The apparent viscosity of the fracturing fluids in Examples 1, 2 and 3 is relatively high. After shearing for 240 minutes, the apparent viscosities are 57 mPa·s, 61 mPa·s and 53 mPa·s, respectively, which are all above the standard value of 50 mPa·s. After shearing for 210 minutes in Comparative Examples 1 and 2, the apparent viscosities drop to below the standard value of 50 mPa·s. Plasma treatment of polyacrylamide and addition of casein to the fracturing fluid can effectively improve the shear resistance of the fracturing fluid.
[0067] Table 1: Apparent viscosity of fracturing fluid at different shear times
[0068]
[0069] As shown in Table 2, the fracturing fluids prepared in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 and 4 were sheared for 60 minutes at 80°C, 100°C, 120°C, 140°C, 160°C and 180°C, and the apparent viscosity of the fracturing fluid was measured. As the shear temperature increased, the apparent viscosity of the fracturing fluid decreased accordingly. The apparent viscosity in Examples 1, 2 and 3 decreased slowly. At 180°C, the apparent viscosities of Examples 1, 2 and 3 were 117 mPa·s, 112 mPa·s and 107 mPa·s, respectively. The apparent viscosity of the fracturing fluids in Comparative Examples 1 and 2 decreased to less than 100 mPa·s at 160°C and to less than 50 mPa·s at 180°C. Plasma treatment of polyacrylamide and addition of casein to the fracturing fluid can effectively improve the high temperature resistance of the fracturing fluid and enhance its thermal stability.
[0070] Table 2: Apparent viscosity of fracturing fluid at different shear temperatures
[0071]
[0072] The fracturing fluids prepared in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 and 4 were tested for resistance reduction according to SY / T 5107-2016 "Method for evaluating performance of water-based fracturing fluids". The results are shown in Figure 2 As shown, the drag reduction rates of the fracturing fluids prepared in Examples 1, 2 and 3 are all above 60%, the drag reduction rate of the fracturing fluids in the comparative examples is lower than that in the examples, and the drag reduction rate of the comparative example 3 is the lowest. 2,5-furan dimethanol can reduce the surface and interfacial tension of the liquid, which helps to improve the fluidity of the fracturing fluid, reduce friction and improve the fracturing efficiency.
[0073] The fracturing fluids prepared in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 and 4 were tested for static sand carrying performance. 50-mesh ceramsite was selected as a proppant, and the ceramsite proppant was added to the fracturing fluid and mixed evenly. The sedimentation rate of the ceramsite proppant was tested for 1 hour, 2 hours and 3 hours. The amount of ceramsite proppant added was 30% of the content of the fracturing fluid. The sedimentation rate of the ceramsite proppant (%) = the content of the ceramsite proppant at the bottom of the sedimentation * 100% / the total amount of the ceramsite proppant. The results are shown in Figure 3 As shown, with the extension of the standing time, the sedimentation rate of the ceramsite proppant increases. After 3 hours, the sedimentation rate of the ceramsite proppant of the fracturing fluid of Examples 1, 2 and 3 is less than 10%, and the sand carrying performance is good. The sedimentation rates of Comparative Examples 1, 2, 3 and 4 reach 11.2%, 24.8%, 13.1% and 30.2% in 3 hours, and the sand carrying performance is poor. Casein can synergize with other chemical substances (such as polymers, cross-linking agents, etc.) to improve the sand carrying capacity of the fracturing fluid. The cross-linking agent is a compound with a maleimide group, which can react with sulfhydryl groups such as cysteine residues in casein to form a stable covalent bond, realize intermolecular cross-linking, form a stable three-dimensional network structure, significantly increase the viscosity and strength of the fracturing fluid, and can more effectively carry and transport the proppant.
[0074] In summary, the integrated pressure-production emulsion fracturing fluid prepared by the present invention has strong shear resistance, high temperature resistance, low friction, strong sand carrying performance, uses environmentally friendly raw materials, has little pollution to the formation, has low production cost, is simple to make, and has broad application prospects.
[0075] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.
Claims
1. A pressure-production integrated emulsion fracturing fluid, It is characterized in that It includes the following components: thickener, cross-linking agent, surfactant; The thickener is prepared by mixing modified polyacrylamide, casein, xanthan gum, konjac gum and water in proportion; The modified polyacrylamide is modified by the following method: placing the polyacrylamide in a plasma equipment treatment chamber, subjecting the polyacrylamide to plasma treatment, wherein the plasma equipment power is 930-950W and the charge density is 950-970 / cm 3 , gas flow rate is 1.2-1.4L / min, processing chamber pressure is 85-90kPa, processing chamber temperature is 58-62℃, and processing time is 160-190s; The casein is prepared by the following method: adding 6.5-6.8% organic acid to skim pure milk, stirring and adjusting the pH value to 4.7-4.8, causing the casein to coagulate and precipitate, filtering and centrifuging to obtain the casein; The cross-linking agent is prepared by mixing disulfide bismaleimide ethane, nano-organic zirconium, nano-organic boron, sodium phosphate and water in proportion; The surfactant is prepared by mixing 2,5-furan dimethanol, alkyl glycoside, alkyl dimethyl betaine, polyethylene glycol and sodium lauryl sulfate in a certain proportion; The organic acid is composed of lactic acid and acetic acid in a mass ratio of 1:1.
2.
2. The integrated pressure-production emulsion fracturing fluid according to claim 1, It is characterized in that Prepared by the following method: S1, thickener preparation: Weigh 30-34 parts by weight of modified polyacrylamide, 28-30 parts by weight of casein, 20-22 parts by weight of xanthan gum, 16-18 parts by weight of konjac gum, and 92-95 parts by weight of water, place in a reactor and mix and stir at a stirring speed of 720-750 rpm for 18-22 minutes to obtain a thickener; S2. Preparation of crosslinking agent: Weigh 20-23 parts by weight of disulfide bismaleimide ethane, 13-16 parts by weight of nano-organic zirconium, 9-10 parts by weight of nano-organic boron, 3-5 parts by weight of sodium phosphate, and 55-60 parts by weight of water, place in a homogenizer and mix to obtain a crosslinking agent solution; S3, surfactant preparation: weigh 18-25 parts by weight of 2,5-furan dimethanol, 12-16 parts by weight of alkyl glycoside, 10-15 parts by weight of alkyl dimethyl betaine, 8-12 parts by weight of polyethylene glycol, and 7-10 parts by weight of sodium lauryl sulfate, and mix them evenly in a blender to obtain a surfactant; S4. Place the thickener prepared by S1 in a reactor, slowly add 45 to 50 parts by weight of the cross-linker solution prepared by S2 into the reactor, mix and stir for 48 to 55 minutes at a stirring speed of 1200 to 1230 rpm, let stand for 30 to 35 minutes, then add 15 to 20 parts by weight of the surfactant prepared by S3, mix and stir for 20 to 25 minutes at a stirring speed of 950 to 980 rpm to obtain an emulsion fracturing fluid.
3. The pressure-production integrated emulsion fracturing fluid according to claim 2, It is characterized in that The reactor temperature is 50-55°C.
4. The pressure-production integrated emulsion fracturing fluid according to claim 2, It is characterized in that The speed of the homogenizer is 500-550 rpm.
5. The pressure-production integrated emulsion fracturing fluid according to claim 1, It is characterized in that The nano-organic zirconium is composed of tetra-n-propyl zirconate and zirconium acetylacetonate in a mass ratio of 1:1, and the nano-organic boron is composed of organic boric acid and organic boron ester in a mass ratio of 1:1.
5.
6. The pressure-production integrated emulsion fracturing fluid according to claim 1, It is characterized in that The particle size of nano-organic zirconium and nano-organic boron is 550-600nm.
7. The integrated pressure-production emulsion fracturing fluid according to claim 1, It is characterized in that The moisture content of casein is 6.5-7.5%.
8. The pressure-production integrated emulsion fracturing fluid according to claim 1, It is characterized in that The particle size of 2,5-furan dimethanol is 500 mesh.
